Finance and HR as Gen Z Stressors: Palangka Raya University Students' Views - Aprilita, Aprilita; Damayanti, Nurlia Eka; Mahrita, Ani (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2025)
In recent years, increasing suicide rates among college students have demonstrated a mental health crisis that needs to be taken seriously. This phenomenon highlights that academic pressure is just one of many social, economic, and cultural pressures that affect students. Therefore, it is important to understand the factors that trigger these issues and provide adequate mental health support. Some suicide incidents involving students in Indonesia emphasize the urgency of addressing this mental health issue. Research shows that life events or stressors, such as stress, anxiety, and depression, have a significant impact on driving suicidal ideation. Factors such as academic pressure, financial burdens, and lack of social support also play an important role in the stress levels experienced by college students. The research